PEMBUATAN PULP UNTUK KERTAS BUNGKUS DARI BAHAN SERAT ALTERNATIF - Dian Anggraini Indrawan; Lisna Efiyanti; Rossi Margareth Tampubolon; Han Roliadi (Jurnal Penelitian Hasil Hutan, 2015)
Indonesia's paper consumption, including wrapping paper, might steadily increase in the future and create challenge for domestic wrapping-paper production due to the dwindling potency of conventional fibrous stuffs (e.g. natural-forest woods). Alternative ligno-cellulosic fibers should be introduced, such as pioneer-tree woods potential for plantation-forest (PF), e.g. jabon and terentang; sengon PF's logging wastes; pulp/ paper mill's sludge; and pineapple-leaf fibers. In relevant, trial on pulp manufacture for wrapping paper was conducted using those alternatives. Initially, each alternative-fiber was examined for their basic properties (i.e. specific gravity, chemical composition, and fiber dimensions/ their derived values). The fibrous pulping employed a hot alk ali semi-chemical process (except sludge). The pulp-sheet with 60 g/ m basis-weight target was 2 formed from the mixture of jabon-wood pulp, terentang-wood pulp, sengon-wood pulp, sludge, and pineapple-leaf pulp (w/ w) in particular proportions; then to each proportion were added additives (alum 2%, clay 5%, wax emulsion 3%, tapioca starch 4%, and rosin soap 3%); and on the resulting pulp-sheets were tested their physical, strength, and optical properties. Results revealed that the proportion regarded as the most prospective for wrapping paper comprised terentang wood pulp (20%), jabon-wood pulp (20%), sengon-wood pulp (40%), and pineapple-leaf pulp (20%). The tolerable proportion for incorporating sludge should comprise sludge (20%), terentang-wood pulp (20%), jabon-wood pulp (20%), sengon-wood pulp (20%), and pineapple-leaf pulp (20%). The presence of harmful/ toxic heavy metals in the sludge which have been strongly indicated should thoroughly be accounted; and hence further experiment on their removal prior to the sludge use for wrapping paper deserves carrying out.